From collective vulnerability to the emancipatory agency of the self - Santiago Urrea Yela; David Osorio-García (Cogent Arts & Humanities)
This article examines the life trajectory of Sonia, a community leader in Colombia, focusing on her responses to vulnerability in contexts of armed conflict and natural disasters. The study was conducted within the Identificarte: Moving with Risk project using a qualitative narrative methodology. Playful and evocative methods were employed to collect data, followed by narrative analysis using the Listening Guide framework. The findings show that Sonia’s vulnerability, rooted in displacement, patriarchal norms, and precarious living conditions, evolved into a process of emancipatory agency. Through her leadership and persistence, Sonia redefined her identity, transforming her experiences into community resilience and social transformation. Her story illustrates how vulnerability can catalyze political and social reconfiguration when supported by social capital and collective action. The article situates Sonia’s trajectory within broader discussions of environmental justice and disaster risk management, highlighting the potential for marginalized communities to reclaim agency and reshape their environments. This case underscores the importance of inclusive institutions and community participation in addressing vulnerability. It also emphasizes the need for policies integrating local voices and experiences in risk management and social assistance to foster transformative, long-term change.